Larger bilateral amygdalar volumes are associated with affective loss experiences - Acosta Henriette; Jansen Andreas; Kircher Tilo (WILEY, 2022)
Affective loss (AL) (i.e., bereavement, relationship breakup) is a stressful life event leading to a heightened risk of developing a psychiatric disorder, for example, depression and anxiety disorder. These disorders have been associated with altered subcortical brain volumes. Little is known though, how AL in healthy subjects is linked to subcortical volumes. In a study with 196 healthy young adults, we probed the association between AL across the individual entire life span, assessed via the List of Threatening Experiences Questionnaire, and magnetic resonance imaging brain gray matter volumes (a priori selected: bilateral amygdalae, hippocampi, thalami; exploratory analyses: nuclei accumbens, caudate, putamina), segmented by use of volBrain. AL was defined as death of a first-degree relative/spouse, close relative/friend, and breakup of a marriage or steady relationship. AL was associated with larger bilateral amygdalar volumes and, after taking into account the total number of ALs, with smaller right hippocampal volumes, both irrespective of sex. Exploratory analyses of striatal volumes yielded an association of AL with larger right nucleus accumbens volumes in men, and increased caudate volumes after the loss of a first-degree relative irrespective of sex. Our data suggest that AL engenders alterations in limbic structures that likely involve processes of chronic stress and amygdala- and hippocampus-dependent fear conditioning, and resemble those observed in general anxiety disorder, childhood maltreatment, and major depressive disorder. Our exploratory findings of striatal volume alterations hint at a modulation of reward processing by AL.